SISTEM SARAF MANUSIA DALAM PERSPEKTIF AL-QUR’AN - Wulan, Adinda Retno; Tanjung, Indayana Febriani; Hasibuan, Eka Khairani (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
This study aims to determine the human nervous system in the perspective of the Qur'an. The method used in this study is a qualitative method with the results of the research in the form of descriptive data obtained using a literature review approach. The results of this study indicate that the brain as the human nervous system has a complex function in regulating all human activities. The brain has a role to control all bodily functions such as thinking, hearing, seeing, behaving and displaying emotions. In the perspective of the Qur'an, the brain and human nervous system are the doors of tadabbur to see the Oneness of Allah SWT. The human brain and nervous system are facilities for thinking and doing actions in order to gain knowledge that can convey piety to Allah SWT.